The shifting sands of time: Maturation and athlete development - Cobley, S.; Romann, M.; Javet, M.; Abbott, S.; Lovell, R. (Talent identification and development in sport. International perspectives, 2021)
In the first two decades of life, notably the years associated with childhood and adolescence, the human body grows an d changes substantially. Physical growth is considered a continuous process with a predictable sequence of changes occurring until full adult maturity at approximately 18-20 years of age for males, and 16-18 years for females. The most observable changes are associated with physical (somatic) body proportions (e.g., height and body mass), although growth encompasses multiple other components, including bone, nerve, and neural network, as well as muscle and fat tissue development (Malina, Bouchard, & Bar-Or, 2004). Considering such changes, this chapter focuses on: (i) highlighting the potential for growth and maturational variability between individuals at similar chronological ages; (ii) outlining the relationships betw een physical maturation and facets of athletic performance; (iii) providing a conceptual model to demonstrate normative growth and maturational related change over time; and (iv) noting the resultant systematic biases in athlete participation, evaluation and selection. In a final section, maturation measurement methods and issues are discussed. These topics are addressed to help establish a clear message - that sports organisations and practitioners need to better understand and account for variability in growth and maturation within their sport systems and athlete development programs.